COMMENTARY ON THE CHANGING NATURE OF EXECUTIVE CONTROL IN PRESCHOOL. Issue 4 (December 2016) - Willoughby, Michael T.
Abstract : In this commentary, I provide a critical evaluation of Espy and colleagues' proposal to use a bifactor modeling approach to characterize children's performance on executive control tasks. I draw attention to an old idea regarding treating items as causal or effect indicators of their latent constructs. I remind readers that factor analytic approaches, including the bifactor model that is proposed here, assume that executive control tasks are effect indicators of the latent construct of executive control. I suggest that executive control tasks may be better conceptualized as causal indicators. I further suggest that these different modeling approaches will result in markedly different conclusions about the nature of executive control—including predictors and outcomes of executive control that were the focus of this monograph.